Eruptive modes and hiatus of volcanism at West Mata seamount, NE Lau basin: 1996–2012 - Robert W. Embley; Susan G. Merle; Edward T. Baker; Kenna H. Rubin; John E. Lupton; Joseph A. Resing; Robert P. Dziak; Marvin D. Lilley; William W. Chadwick Jr.; T. Shank; Ron Greene; Sharon L. Walker; et al. (Geochemistry, Geophysics, Geosystems)
Abstract We present multiple lines of evidence for years to decade‐long changes in the location and character of volcanic activity at West Mata seamount in the NE Lau basin over a 16 year period, and a hiatus in summit eruptions from early 2011 to at least September 2012. Boninite lava and pyroclasts were observed erupting from its summit in 2009, and hydroacoustic data from a succession of hydrophones moored nearby show near‐continuous eruptive activity from January 2009 to early 2011. Successive differencing of seven multibeam bathymetric surveys of the volcano made in the 1996–2012 period reveals a pattern of extended constructional volcanism on the summit and northwest flank punctuated by eruptions along the volcano's WSW rift zone (WSWRZ). Away from the summit, the volumetrically largest eruption during the observational period occurred between May 2010 and November 2011 at ∼2920 m depth near the base of the WSWRZ. The (nearly) equally long ENE rift zone did not experience any volcanic activity during the 1996–2012 period. The cessation of summit volcanism recorded on the moored hydrophone was accompanied or followed by the formation of a small summit crater and a landslide on the eastern flank. Water column sensors, analysis of gas samples in the overlying hydrothermal plume and dives with a remotely operated vehicle in September 2012 confirmed that the summit eruption had ceased. Based on the historical eruption rates calculated using the bathymetric differencing technique, the volcano could be as young as several thousand years.